Hydrocracking of Coconut Oil on the NiO/Silica-Rich Zeolite Synthesized Using a Quaternary Ammonium Surfactant - Sriatun Sriatun; Heru Susanto; Widayat Widayat; Adi Darmawan (Indonesian Journal of Chemistry, 2021)
NiO/silica-rich zeolite catalysts were used for coconut oil hydrocracking. The catalyst was prepared with a mixture of Na2SiO3, Al(OH)3, NaOH, and quaternary ammonium surfactants. The surfactant was varied of types like as tetrapropylammonium bromide (TPAB) and cetyltrimethylammonium bromide (CTAB). The acidity of the silica-rich sodalite zeolites enhances with the increase in nickel oxide added through a wet impregnation. The hydrocracking process was carried out by a semi-batch method. Liquid products were analyzed using GC-MS. The results showed that the addition of surfactants increased the catalyst surface area and acidity. Meanwhile, the presence of nickel oxide increases the acidity of the catalyst. The hydrocracking results showed an increase in gas products when the surface area was high, i.e., 23.781% in silica-rich sodalite zeolite without template (Z), 32.68% in silica-rich sodalite zeolite with tetrapropylammonium (ZTPA), and 39.673% in silica-rich sodalite zeolite with cetyltrimethylammonium (ZCTA). The presence of NiO increased the liquid product and the selectivity of the bioavtur fraction (C10-C15), where the highest percentage of liquid product was 60.07% at NiO/ZTPA.